The Olahan Potensi Alam Anti Stunting : Pendampingan Komunitas Ibu Giat Di Desa Kedungrejo Kecamatan Pakis Kabupaten Malang - Zuraidah, Zuraidah Zuraidah (Universitas Gajah Putih, Indonesia, 2025)
Stunting is a serious health issue that impacts the physical growth and cognitive development of children. Kedungrejo Village, located in Pakis Sub-district, Malang Regency, is one of the villages at high risk of stunting due to nutritional issues affecting pregnant women and toddlers. This community service program aims to utilize local natural resources to improve the nutritional intake of mothers and children through nutritious food processing. The program involves the Komunitas Ibu Giat, a group of housewives actively engaged in community empowerment activities. Assistance is provided through training in the processing of nutrient-rich local food ingredients, especially those that can help prevent stunting. The outcomes of this activity show an increase in knowledge, skills, and active participation of mothers in providing nutritious food for their families.